Comparison of the significance of CD4+ and CD8+ T lymphocytes in the protection of mice against Encephalitozoon cuniculi infection - Braunfuchsová, Pavlína; Salát, Jirí; Kopecký, Jan (The Journal of parasitology, 2002)
The role of T lymphocyte subpopulations in the protection against intraperitoneal (i.p.) and peroral Encephalitozoon cuniculi infections was compared in adoptive-transfer experiments using severe combined immunodeficient mice. Whereas CD8+ T cell-depleted, but not CD4+ T cell-depleted, BALB/c splenocytes failed to protect the mice against i.p. infection, only SCID mice reconstituted with both CD4+ T lymphocyte- and CD8+ T lymphocyte-depleted splenocytes succumbed to peroral infection. The results indicate that whereas CD8+ T cells are critical for the protection against an i.p. E. cuniculi infection, both CD4+ and CD8+ T lymphocyte subpopulations play a substantive protective role in a peroral infection, i.e., natural route of infection.
Keywords: Animals; Encephalitozoonosis; myši SCID; slezina; Mice; převzatá imunita; CD8-Positive T-Lymphocytes; Adoptive Transfer; Mice, Inbred BALB C; Mice, SCID; myši; Encephalitozoon cuniculi; CD8-pozitivní T-lymfocyty; modely nemocí na zvířatech; myši inbrední BALB C; Spleen; Disease Models, Animal; CD4-Positive T-Lymphocytes; zvířata; encephalitozoonóza; CD4-pozitivní T-lymfocyty